Tinjauan Historis Bekarang: Warisan Budaya untuk Alam di Kecamatan Kikim Timur, Kabupaten Lahat - Dhita SBK, Aulia Novemy; Dewo, Mutiara Kencana; Marantika, Raficko Deny (Journal of Indonesian History, 2020)
dominated by rivers, influences the culture of its people such as bekarang which is a cultural heritage to preserve the ecosystem in the river. The puspose and benefits of this research are to reveal the historical present, describe current developments at this time and local wisdom value in bekarang. The method are used is historical method which includes the heurictic, source criticism, interpretation and historiography. The result showed that based on historical studies, now including activities that have been cariied out by humans in the pre-literacy period. This is consistent with the concept of life in pre-literate societis that depended on nature and settlements nears river. So they take advantages of these conditions to make ends meet. Bekarang is a cultural for nature thas is still being practiced, especially by people in Gelumbang and Gunung Kembang villages, District of Kikim Timur, Lahat Regency. Bekarang is a cultural heritage that deserves to be preserved, especially in the geographical conditions of South Sumatra which are dominated by rivers